Nilai-Nilai Pendidikan Islam dalam Permainan Tradisional Bugis Mappadendang - Sarifa Suhra (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This paper focuses on the traditional game of mappadendang and reveals the values ​​of Islamic education and gender equality in the traditional Bugis mappadendang game. Method; Qualitative research with pedagogical and sociological approaches is applied using observation, interviews, and FGD (Forum Group Discussion) with selected players, audiences, government, and community leaders. Empirical data illustrates that the mappadendang game is still preserved today through folk party events and contains Islamic education values. Findings; This study found various values ​​of Islamic education contained in the traditional mappadendang game, namely, patient (sabbara), compact (asseddi seddingeng), cooperation, hard work (reso temmangingi), and creativity (macaradde). This game is also loaded with the value of gender equality seen in women and men's involvement. The preservation of this game is urgent to create a civilized and gender- just Bugis society in various life dimensions.